2022
DOI: 10.3390/children9121835
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Surgically Accelerated Orthodontic Techniques: A Systematic Review

Abstract: Evidence on the potential adverse effects of surgically accelerated orthodontic techniques is scarce. The aim of this review was to evaluate the available scientific evidence regarding the adverse effects on periodontium, tooth vitality, and root resorption, associated with these surgical procedures in children, adolescents, and adults. The reporting of this review was based on the PRISMA2020 guidelines. Seven databases and three registers were searched for randomized clinical trials (RCTs) and controlled clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…A prior study suggested that surgically accelerated orthodontic methods did not produce notable negative impacts on the periodontium, root length, or tooth vitality [51]. Another report demonstrated similar adverse effects associated with both surgical and non-surgical interventions [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior study suggested that surgically accelerated orthodontic methods did not produce notable negative impacts on the periodontium, root length, or tooth vitality [51]. Another report demonstrated similar adverse effects associated with both surgical and non-surgical interventions [52].…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography has been integrated with the piezocision method to allow for computer-aided design, and computeraided surgical guides aim at averting inadvertent harm by enabling real-time tracking of the piezoelectric instruments during the surgical process [59]. The performance of high-quality clinical trials with reduced bias potential is recommended to draw dependable conclusions about the adverse consequences of the surgical procedures used to expedite orthodontic treatment in individuals of various age groups [51].…”
Section: Discussionmentioning
confidence: 99%
“…Two periodontic techniques-piezocision and micro-osteoperforation-are less invasive when compared to other surgical techniques like Wilkodontics and corticotomy. The acceptance of corticotomies is still low because both clinicians and patients consider them to be too invasive [15][16][17]. To solve this issue, a new minimally invasive surgical technique known as piezocision was created.…”
Section: Introductionmentioning
confidence: 99%